Bacillus cereus EC9 protects tomato against Fusarium wilt through JA/ET-activated immunity - Pazarlar, Sercan; Madriz-Ordeñana, Kenneth; Thordal-Christensen, Hans (Frontiers in Plant Science, 2022)
The mechanisms of action and the limitations of effectiveness of natural biocontrol agents should be determined in order to convert them into end products that can be used in practice. Rhizosphere Bacillus spp. protect plants from various pathogens by displaying several modes of action. However, the ability of Bacillus spp. to control plant diseases depends on the interaction between the bacteria, host, and pathogen, and the environmental conditions. We found that soil drenching of tomato plants with the non-antifungal Bacillus cereus strain EC9 (EC9) enhances plant defense against Fusarium oxysporum f. sp. lycopersici (Fol). To study the involvement of plant defense-related phytohormones in the regulation of EC9-activated protection against Fol, we conducted plant bioassays in tomato genotypes impaired in salicylic acid (SA) accumulation, jasmonic acid (JA) biosynthesis, and ethylene (ET) production, and analyzed the transcript levels of pathways-related marker genes. Our results indicate that JA/ET-dependent signaling is required for EC9-mediated protection against Fol in tomato. We provide evidence that EC9 primes tomato plants for enhanced expression of proteinase inhibitor I (PI-I) and ethylene receptor 4 (ETR4). Moreover, we demonstrated that EC9 induces callose deposition in tomato roots. Understanding the involvement of defense-related phytohormones in EC9-mediated defense against Fusarium wilt has increased our knowledge of interactions between non-antifungal plant defense-inducing rhizobacteria and plants.